Zero dimensional iodobismuthate: Synthesis and optical property. (2022) - Pandey, Souvik; Roy Choudhuri, Jyoti
Abstract: 0-D hybrid materials are of synthetic interest due to their photovoltaic efficiency. These inorganic-organic hybrid materials also exhibit ferroelastic, ferroelectric and non-linear optical properties. An inorganic-organic hybrid material where inorganic counter-part [Bi2 I9 ] 3− stabilized by counter 8-aminoquinolinium cations has been synthesized and characterised by single crystal XRD, IR spectroscopy and elemental analysis. Its thermal property and optical band gap also have been studied and discussed here.